Capacity for knowledge-based smallholder agriculture in Ethiopia: Linking graduate programs to market-oriented agricultural development: Challenges, opportunities and IPMS experience - Lemma, T.; Tegegne, Azage; Hoekstra, Dirk (International Livestock Research Institute, 2012)
Graduate Programs in agriculture and allied disciplines in Ethiopia (henceforth the GPs) are expected to make concrete contributions towards achieving market-led and knowledge-based transformation of smallholder agriculture. To that end, strengthening capacities of the GPs and linking them to development deserve due policy attention. No panacea exists, however, as to how the programs can be better strengthened, linked, and become more responsive. Lessons from initiatives on the ground in the country and beyond are thus crucial to inform policy and the development of context specific innovative strategies. This paper aims to make a modest contribution to the discourse in Ethiopia and beyond on transforming GPs related to agriculture into ‘developmental institutions’. The paper highlights the imperatives for knowledge-based transformation of smallholder agriculture in Ethiopia and emerging roles of GPs; discusses key challenges of the GPs to realize their mandates and to meet ever changing expectations. It also presents a case study of an initiative by +aimed at linking GPs through research by students to commodity value chain development and actors, and discusses qualitative and quantitative indicators of outcome in terms of enhanced research and learning experience. The paper draws out some lessons and identifies strategic and practical options, including from the review of good practices elsewhere, that may help to improve learning and research in the GPs. The analysis shows that the GPs are currently facing several challenges, which could not be solved by government or by the programs alone, but rather require multiple linkages and collaborations. The GPs, on the one hand, need to be more proactive in creating linkages and partnering with regional and federal governments, and with development/interventions, and, on the other, actors who are truly committed to sustainability should be more willing to integrate systematically into development programs, as a critical component, partnering with and strengthening capacity of key capacity building national institutions, such as the GPs. Revitalizing the programs calls for holistic approach from an innovation systems perspective, multipronged and multi-level strategies, and long-term commitments.